Local Economic Resistance and the Struggle Against Global Capitalism: Evidence from the Rammang-Rammang Tourism Area - Hana Tuo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Contemporary economic systems increasingly prioritize accumulation and growth, reshaping social and cultural sectors, including tourism. While tourism is often promoted as a development strategy capable of generating prosperity, its market-oriented orientation frequently reproduces social inequalities and uneven economic benefits at the local level. This article examines the transformation of the local economy in the Rammang-Rammang tourism area, South Sulawesi, following community resistance against karst mining in 2007. Drawing on a critical qualitative approach, the study employs Critical Discourse Analysis (CDA) following Norman Fairclough’s framework to analyze how narratives of community-based tourism, empowerment, and local economy are produced, negotiated, and contested. Data were collected through in-depth interviews, participant observation, and documentation of policy texts, media narratives, and discursive artefacts related to tourism development. The findings indicate that post-resistance economic transformation in Rammang-Rammang does not evolve linearly toward an egalitarian community economy. Instead, tourism development becomes a contested arena in which collective practices and everyday forms of resistance coexist with emerging inequalities, concentration of economic access, and tendencies toward local capitalism. Although community-based economic practices and subsistence activities continue to function as mechanisms of autonomy and resistance, they remain fragmented and vulnerable to discursive and structural co-optation. This study argues that community-based tourism should be understood not as a purely alternative economic model, but as a dynamic space of negotiation between resistance, adaptation, and capitalist domination. The article contributes to critical debates on counter-economy, power relations, and equitable development in tourism-based communities in the Global South.